Antithrombotic strategies after transcatheter aortic valve replacement a network meta-analysis - Mengxiao Shi; Ying Wu; Qing Zhou; Qing Zhou (Frontiers in Cardiovascular Medicine)
The optimal antithrombotic regimen for patients without an indication for oral anticoagulation (OAC) after transcatheter aortic valve replacement (TAVR) remains unclear. We conducted a network meta-analysis of randomized controlled trials to clarify the best postoperative antithrombotic regimen. We searched literature databases including PubMed/Medline and Cochrane up to June 2024. Safety endpoints included all-cause death, cardiovascular death, major/life-threatening bleeding, and minor bleeding during follow-up. Efficacy endpoints encompassed ischaemic stroke transient ischemic attack (TIA), systemic embolism, hypoattenuated leaflet thickening (HALT), and reduced leaflet motion (RELM). Outcomes were assessed during the follow-up period specified in each trial (range:3–24 months). The results were statistically analyzed using R 4.3.2 and Stata 16 software. The final analysis included seven randomized controlled trials. Single antiplatelet therapy (SAPT) showed a lower incidence of major/life-threatening bleeding compared to the direct oral anticoagulants (DOACs) group (OR: 0.68, 95% CI: 0.47–0.99, P = 0.002) during the 3–24 month post-TAVR period. However, no significant differences were found in other safety or efficacy endpoints. SAPT is the preferred treatment strategy for TAVR patients without anticoagulation indications.Systematic Review Registrationidentifier, PROSPERO registration number: CRD42024584735.